Refleksi Pragmatisme terhadap Motivasi Belajar Matematika Siswa dalam Logika dan Cinta di Drama Korea - Wulansari, Tantya; Rani, Rani; Wahidin, Didin; Firmansyah, Eka (STKIP PGRI SITUBONDO, 2024)
The impact of Covid-19 throughout the world has resulted in a decrease in students' motivation to learn mathematics. At that time , everyone was doing activities at home so students used gadgets to study which resulted in students being exposed to Hallyu. Hallyu is a culture in South Korea. South Korea is one of the countries that is currently the center of attention in cyberspace. In the current Gen Z generation, they prefer actors or artists from that country. This research analyzes the relationship between logic and love in Korean dramas on students' mathematics learning motivation using a pragmatism approach. By watching one of the Korean drama content entitled